HPB P36 The influence of sarcopenia and systemic inflammation on survival in resected pancreatic cancer. (7th December 2022) - Bryce, Adam; Dreyer, Stephan; Froeling, Fieke; Dolan, Ross; Chang, David
Abstract: Background: Sarcopenia, cachexia and systemic inflammation are early hallmarks of pancreatic cancer (PC) which hamper systemic therapy and accelerate the terminal stages of the disease. The significant impact of sarcopenia on survival in PC has been demonstrated in numerous meta-analyses using standardised thresholds to define body composition measurements. We sought to determine the influence of sarcopenia and systemic inflammation on survival in our cohort of resected PC patients. We also interrogated the impact of the introduction of neoadjuvant therapy (NAT) protocols on survival, body composition and systemic inflammation. Finally we investigated the use of varying thresholds to define sarcopenia and the impact of this on survival. Methods: Analysis of a prospectively maintained database of resected patients with PC accrued through the tertiary West of Scotland Pancreatic Unit was undertaken. Patients with cancer types other than pancreatic ductal adenocarcinoma were excluded. Body composition analysis was carried out using cross-sectional measurements of skeletal muscle area, skeletal muscle density and visceral fat area at the L3 level from pre-treatment or pre-operative CT scan using Slice-o-Matic software (Tomovision, Montreal). Disease-specific survival was used with Log-rank test for survival differences. Results: 188 patients underwent resection between 2008–2020. 44.1% received NAT and 65.9% were resected up-front. Using Prado / Martin cutoffs of skeletal muscle index (SMI) to define sarcopenia demonstrated no significant survival difference in either cohort. Visceral obesity and myosteatosis (defined by Doyle / Martin) also demonstrated no significant survival difference. Modified thresholds tailored to our cohort were used and a median survival difference of 34.5 vs 23.1 months was identified (p < 0.001). Similarly for modified BMI-specific thresholds a median survival difference of 35.2 vs 22.8 months was identified (p < 0.001). On further analysis of the NAT cohort, 60.2% of patients exhibited gain in SMI with treatment and 39.8% of patients exhibited loss of SMI. There was a tendency towards poorer survival in the latter group however this was not significant. On further stratification of cohorts in to NAT and up-front resection it was revealed that the predictive effect of sarcopenia was entirely the effect of the up-front resected cohort, with little difference in survival between sarcopenic and non-sarcopenic groups in the NAT cohort. Median survival in all patients (NAT and up-front resection combined) increased from 27.4 months to 32.6 months (p = 0.016) with the introduction of NAT protocols in 2013. Conclusions: Defining sarcopenia using modified thresholds tailored specifically to our cohort of patients demonstrates the significant impact of sarcopenia on survival in resected PC. The introduction of NAT protocols in 2013 has had a significant impact on survival, an effect which may be due to the selection of smaller tumours for up-front resection. Further work is needed as part of intention-to-treat analysis to identify patients who undergo NAT who do not progress to resection. Analysis of this cohort will validate our findings and shed further light on the impact of neoadjuvant therapy on sarcopenia and body composition. This analysis is ongoing and further novel data will be presented in September should this abstract be accepted.